Powdered activated carbon for removal of phenol and treatment of palm oil mill final effluent - Ashraf, Qazi Mamoon; Kabbashi, Nassereldeen Ahmed; Alam, Md Zahangir; Muyibi, Suleyman Aremu; Ameen, Emad S.M.; Olanrewaju, Rashidah Funke (IIUM Press, International Islamic University Malaysia, 2017)
Empty fruit bunch (EFB) is one of the most abundant residues of the palm oil mill industry. Most of it left unused and being disposed to the landfill. Discharging the huge volume of empty fruit bunch (EFB) in a sanitary landfill will not only occupy a great deal of land but also conveys an inherent potential for pollution of indigenous water resources. Moreover, palm oil processing requires large quantities of water results in palm oil mill effluent, which contains a high concentration of phenolic compounds. Thus, it must be managed with extreme care to avoid adverse environmental or human health impacts. The aim of this study was to investigate the feasibility and the potential of converting palm oil industrial residue namely empty fruit bunch (EFB) into activated carbon. Powdered activated carbon samples were produced from oil palm empty fruit bunches (EFB) by varying the operating parameters of temperatures, CO2 gas flow rates and activation times using 2-level full factorial experimental design. The prepared EFB samples were carbonized for 30 minutes using nitrogen gas, followed by activation with CO2 gas. The optimum preparation conditions for PAC samples produced were investigated through adsorption tests on an aqueous solution of phenol. Characterizations of the best quality AC sample prepared and the optimum conditions for adsorption of phenol were determined. Freundlich and Langmuir adsorption isotherms, as well as pseudo first order and second order adsorption kinetics models on prepared AC were studied. Finally, evaluation of the adsorption efficiency of the EFB based-AC was investigated in palm oil mill final effluent (POMFE) using a bench-scale model.